Interpreting Isaiah the suffering and the glory of the Messiah - Wolf, Herbert M. (Grand Rapids, MI Zondervan, 1985)
Includes bibliographical refrences and index.
Keywords: Bible. O.T. Isaiah -- criticism, interpretation, etc